Hubungan Stereotipe Gender Terhadap Major Satisfaction Mahasiswa Keperawatan di Kota Kediri: The Relationship Between Gender Stereotypes And Major Satisfaction Among Nursing Students In Kediri - Mohammad Rafi Firdaus; Wildan Akasyah; Bagus Sholeh Apriyanto Apriyanto; Marianingsih (Jenggala : Jurnal Riset Pengembangan dan Pelayanan Kesehatan, 2026)
The nursing profession is dominated by women who have become a social phenomenon. Culturally and behaviorally in society, nursing is feminine and inappropriate for men. There are 532,935 health students with 165,209 (30.57%) nursing students in Indonesia. The phenomenon that occurs is that there is a prevalence of 45-52% of male students in nursing study programs in Indonesia. Using a quantitative non-experimental cross-sectional study design. Sampling using a simple random sampling technique of 96 respondents. Data collection of gender stereotypes using the SGQ questionnaire and major satisfaction data using AMSS. Data were analyzed using the Spearman's rho test. The results showed that the level of gender stereotypes in the low category was 66.67% and major satisfaction in the low category was 62.5%. The results of the Spearman's rho test showed a significance value of the level of gender stereotypes and major satis faction of 0.000 <0.05, with a fairly strong positive correlation direction. So H1 is accepted and H0 is rejected, meaning there is a relationship between gender stereotypes and major satisfaction of nursing students in Kediri City. Based on the results of the study, it is suggested that institutions can develop programs that help students understand the reality of the nursing profession so that they have more realistic expectations of the chosen major. For educational institutions, it is suggested to hold seminars or training related to gender equality in nursing to improve students' understanding of their professional roles. For the nursing profession, it is suggested to be more active in campaigning that this field is open to all genders. For further researchers, it is suggested that further researchers conduct a more in-depth study of other factors that can moderate the relationship between gender stereotypes and major satisfaction.